The Effect of Scattering of Phonons, Surface and Grain Boundary on electrical Properties for Tungsten Nanometallic - Alzobaie, Ammar R.; Mohammed , May A.; Abdul Amir , Haider F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
In the context of increasing the use of nanometals in electrical and electronic applications and improving their unique electrical properties, this research explains the effect of the mechanisms of scattering of phonons at room-temperature (293K) in addition to the scattering and reflection of electrons at the surface and at grain boundary on the electrical resistivity of Tungsten metal at different thicknesses. The electrical resistivity of Tungsten was obtained by solving the Boltzmann transport equation which the electron scattering coefficient at the surface (p) is calculated by the Fuch-Sondheimer model, and the grain boundary reflection coefficient (R) by the Mayadas-Shatzkes model were calculated as (p=0.89) and (R=0.18) for Tungsten metal based on the mean of the free path of the electrons. The results showed that there is a linear relationship between the mechanisms of scattering and resistivity, and an inverse relation between electrical resistivity (ρ) and the thickness of the nanometal (d) and extending to a large range of thicknesses. Moreover, the defects of the crystal lattice and the roughness of the surface have an evident impact on the electrical properties of Tungsten metal. In addition, we obtained an excellent consistency between experimental data and theoretical results of electrical resistivity. These results provide important predictions for the use of nano-Tungsten as an interconnection between micro integrated electronic circuits and in various electrical devices